Costs and Burden Associated With Loss of Labor Productivity in Informal Caregivers of People With Dementia: Results From Spain. Issue 5 (May 2018) - Farré, Marta; Kostov, Belchin; Haro, Josep Maria; Cabrera, Esther; Risco, Ester; Alvira, MCarmen; Miguel, Susana; Zabalegui, Adelaida
Abstract : Aims: We analyzed indirect costs related to loss of labor productivity (LLP) in informal caregivers (ICs) of people with dementia (PwD) and the associated caregiver burden and patients' clinical variables. Methods: Multicenter cohort study of PwD and their ICs ( n = 287) focused on two groups: (1) home care and (2) institutional long-term care. The costs of LLP were assessed using the Resource Utilization Dementia instrument and a human capital approach. Results: The cost for LLP was 378[Euro sign]/month or 4.536[Euro sign]/year. Greater disease severity increased the likelihood of reducing working hours and missing a working day. There was a significant association between partial absenteeism and burden in employed informal caregiver in both the home and institutional setting. Conclusion: Cognitive impairment contributes to the cost of LLP in IC especially in home-care. LLP has a negative impact on IC burden.